The Impact of Sovereign Credit - Ntswane, Lesley (My University, 2011)
This event study investigates the impact of sovereign credit ratings action on the foreign exchange rate in South Africa. The study uses the mean adjusted return model to establish the impact sovereign credit rating announcements by three rating agencies on the South African Rand against the American Dollar daily exchange rate and volatility between 1994 and 2007. While previous studies, especially after the notable depreciation and subsequent recovery of the South African Rand, in 1998 and 2001-2002, have tried to identify the determinants of the Rand exchange rate, none of the studies has taken sovereign credit rating actions into account. The results from this study have shown that sovereign credit rating announcements by Standard and Poor’s have a statistically significant impact on the South African Rand exchange rate against the American Dollar. The impact was however not only positive during an upgrade as previously found in a similar study on foreign exchange rate, but negative excess returns were also computed during the event window period. Rating action announcements by Fitch and Moody’s on the other hand, do not have any significant impact on the on the South African Rand exchange rate against the American Dollar. The sovereign credit rating announcements were, however, found to have insignificant impact on the foreign exchange rate volatility during the event window period. The study also found that sovereign credit ratings announcements have no significant impact on the gap between nominal exchange rate and the PPP equilibrium exchange rate. This may be a confirmation that sovereign rating action is not one of the factors that influence the speed towards mean reversion to close the arbitrage created by price differences in the long-run exchange rate measure through PPP. What also stood out in this study was that in the period when the South African Rand experienced the highest depreciation against the American dollar in 2001, none of the rating agencies issued prior negative announcements. In fact the iii South African rating was raised after the recovery of the Rand between 2002 and 2003. The findings from this study, however, open an opportunity for further studies. South Africa’s rating announcements between 1994 and 2007 provides only positive sovereign rating announcements. Previous studies have shown that the rating announcements had a significant effect on bond and stock prices where an announcement was a downgrade and especially for below investment grade rated securities. In addition to that, the only time an effect was noticed for an upgrade was when a rated sovereign moved from below investment to investment grade. Significant negative exchange rate reaction has also been found during a downgrade, for below investment sovereigns. This may explain the lower significant level impact on the exchange rate in the investment graded South Africa. It would be interesting to see a mix of rating announcements especially for developing economies such as South Africa. This presents an opportunity for further studies on the impact of sovereign credit ratings on exchange rates in developing economies and especially those that have experienced large currency depreciation in recent times
MBA - WBS
Keywords: Sovereign credit ratings; Foreign exchange